Analysis of Increasing Product Sales Value Through Sustainable Business Planning in MSMEs in Medan City - Eli Safrida; Selfi Afriani Gultom; Raya Puspita Sari Hasibuan; Suri Purnami; Ana Fitria; Susilawati Susilawati (International Journal Labs, 2024)
This study aims to analyze the increase in product selling value through sustainable business planning in Micro, Small, and Medium Enterprises (MSMEs) in Medan City, especially those engaged in handicrafts. The majority of MSMEs in this sector are known to face challenges in the sustainability of their businesses due to the lack of effective business planning. This research method involves in-depth surveys and interviews with a number of handicraft MSMEs in Medan City, namely a total of 36 MSMEs. The collected data will be analyzed using qualitative and quantitative approaches. The results of this analysis will provide a comprehensive overview of the obstacles faced by MSMEs in managing their businesses, especially related to aspects of business planning. This research highlights the need for better business planning as the key to increasing the selling value of MSME products. By formulating a sustainable business plan, it is hoped that MSMEs can identify and overcome problems that often arise in their business activities. In addition, this study also explores the positive impact of sustainable business planning on increasing the competitiveness and marketing of MSME products. The results of this study are expected to provide practical recommendations to handicraft MSMEs in Medan City, as well as to related stakeholders, such as local governments and MSME supporting institutions. The implementation of sustainable business planning is expected to make a significant contribution to increasing the selling value of MSME products and in turn, improving the welfare of MSME owners and economic growth in the region. Thus, it can be understood that careful business planning is indeed very important.